Antibacterial Activity of Gel of Ethanol Extract of Papaya Leaves (Carica papaya L.) againts Propionobacterium acnes - Pertiwi, Dewi; Ihsanul Hafiz; Rahmalia Salma (Talenta Publisher, 2019)
Abstract Papaya plants (Carica papaya L) besides being a food ingredient are also believed to have medicinal properties and are used traditionally, one of which is in dealing with acne problems. The purpose of this study was to formulate papaya leaf extract in the form of a gel preparation and test its antibacterial activity against the Propionibacterium acnes bacteria. The preparation of the ethanol extract of papaya leaves was made in three concentrations namely 5, 10 and 15%, then tested for antibacterial activity and compared with negative controls (blank gel) and positive control (erythromycin). The results showed that the papaya extract ethanol extract of 10 and 15% leaves had significantly different activities to the negative controls, but the 5% gel formula did not show any different activity towards negative controls. The conclusion of this study is that active papaya leaf ethanol extract gel inhibits bacterial growth at concentrations of 10 and 15%. Keywords: Carica papaya L., gel formula, antibaterial activity, Propionibacterium acnes